Design of a Docking Wall-Climbing Robot. (1st February 2013) - Liu, Rong; Liang, Ran
This paper introduces an innovative wall-climbing robot. The robot consists of two single-body negative pressure adsorption robots which could dock together as a mother-robot or separate into two independent child-robots. The child-robots connect with each other through a docking mechanism which can not only lock solidly and unlock smoothly but which can also adjust the relative position of the two child-robots. This design guarantees that while in dock mode the mother robot will be able to cross some barriers which are impossible to surmount for a single-body wall-climbing robot, while in separate mode the child-robots maintain agility and mobility compared to other two-body robots. In this paper, an overview of the mechanical structure of the robot is first presented and then three possible mechanisms for barrier-crossing are discussed and a reasonable one is selected. An analysis of the initial docking condition of the selected design is also given which provides the basis for the experiments and research for the future.